Parents Evaluation of Developmental Status and Denver Developmental Screening Test II in high risk infant and toddler - Effie Koesnandar; Soedjatmiko Soedjatmiko; Pustika Amalia (Indonesian Pediatric Society, 2010)
Background. Developmental screening is important particularly for high risk infants and toddlers. Parents Evaluation of Developmental Status (PEDS) and Denver Developmental Screening Test II (Denver II test) are recommended instruments with good sensitivity and specificity. Compared to Denver II test, PEDS is simpler, thus it is important to assess the agreement of PEDS and Denver II test.Objectives. To determine the prevalence of developmental disorder in high risk infants and toddlers and agreement of PEDS and Denver II test.Methods. Infants and toddlers registered at pediatric high risk clinic were recruited. PEDS questionnaire was answered by parents while the Denver II test performed by the investgator. Agreement of PEDS and Denver II instrument was assessed by Kappa score.Results. Out of 71 subjects, 41 (58%) were male, 43 (61%) were >12 months old, 35 (49%) were undernourished, 42 (59%) were preterm (<37 week gestational age), and 43 (60.6%) were low birth weight (LBW). The prevalence of developmental disorder was higher in subjects >12 months old (42%), undernourished (49%), preterm (48%), and LBW (47%). The prevalence of developmental disorder was 49% by PEDS and 39% by Denver II test. Agreement of PEDS and Denver II test was good with Kappa score 0.52, particularly for gross motor and language domain.Conclusions. The prevalence of developmental disorder is higher in high risk infant and toddler, who >12 months old, undernourished, premature, and LBW. PEDS instrument are equivalent to Denver II test, shows good agreement, particularly for gross motor and language domain. [Paediatr Indones. 2010;50:26-30].